Restoration of Degraded Agricultural Land - Alex, Saturday (Ommega Publishers, 2018)
Restoration of agricultural land is important for sustainability of agriculture and environment. Land is under immense pressure due to ever increasing population thereby ensuing growing demand for food, fiber and shelter. Agricultural land is being deteriorated due to different anthropogenic and natural factors. The basic factors causing soil erosion- induced degradation are wind and water erosion. Acidification, compaction and salinization are some other causes of agricultural land degradation. The main causes of erosion on agricultural land are intensive cultivation, overgrazing, poor management of arable soils and deforestation. Restoration of eroded agricultural land is achieved through several agronomic and biological techniques. Crop rotations, agro-forestry, reduced tillage, cover crops, vegetative filter strips, residue, and no-till are important among these. Biological measures such as buffers, conditioner application in direct contact with the soil surface, crop residues using manure protect the soil from erosion. Restoration of saline agricultural land can be achieved through recharge stabilization and reconstruction of saline land through fencing, retain remnant vegetation, revegetation, runoff interception earthworks, and water table lowering.